A ingestão de pescado e as concentrações de mercúrio em famílias de pescadores de Imperatriz (MA) - MILHOMEM FILHO, Edem Oliveira (Universidade Federal do Pará, 2017)
Introduction: Significant levels of mercury exposure associated with fish intake have been demonstrated in riverine populations living in areas of mineral exploration as the basin of Tapajós and Madeira. In the Tocantins region, although few studies, there is no evidence of human exposure through food. Objective: To assess the levels of exposure to mercury in resident fishermen families in the riverside area of the middle Tocantins and to quantify the levels in fish consumed by these families. Methods: We conducted a cross‑sectional study involving families of Beira Rio community fishermen, located on the Tocantins riverbanks in the city of Imperatriz, Maranhão. Brazil. Data were collected from socio‑demographic and food profile, as well as samples of fish and hair, which were analyzed by atomic absorption spectrophotometry. Results: The socio‑demographic profile of families studied was common to the local population located in other basins. The food profile did not run the default rule, with the fish being the primary dietary protein source. The species of piscivorous and zooplancton habits had the highest mercury concentrations, and the mean values were 0.2775 µg/g in fish‑dog and 0.1360 µg/g in mapará. Among the 25 families evaluated, the lowest average concentration of family was 0.186 ± 0.043 µg/g and the higher was 5.477 ± 2.896 µg/g. Conclusion: Fishing families have low mercury exposure levels in the same order of magnitude, probably because of the food consumption of fish, including piscivorous species, which were found to be below the safe upper limit for human consumption established by Brazilian standards. This serves as a reference for other studies.